PSYCHOSOCIAL REPERCUSSIONS OF RADIOTHERAPY TREATMENT FOR CERVICAL CANCER: A QUALITATIVE APPROACH - Pimentel, Natalia Beatriz Lima; Modesto, Felipe Cardoso; Lima, Vivian Cristina Gama Souza; Oliveira, Adriana Maria de; Andrade, Karla Biancha Silva de; Fuly, Patrícia dos Santos Claro; Santos, Mauro Salvador Caldeira dos (Cogitare Enfermagem, 2023)
Objective: to understand the psychosocial repercussions of post radiotherapy treatment for cervical cancer. Method: qualitative study, with the participation of patients in post radiotherapy treatment for cervical cancer in an onco-gynecologic nursing outpatient clinic, located in the Municipality of Rio de Janeiro - Brazil. Data were collected during the months of March and April 2019 by means of open interview and submitted to content analysis. Results: four categories were defined: the construct of social roles: the loss of female identity; the sexuality of post-treated women for cervical cancer: marital repercussions; difficulties in adapting to the new life condition: rebuilding the body image; living with cervical cancer: rethinking life and rebuilding values through the support network. Final considerations: the results contribute to the direction of care, increasing the quality of life and helping these women reorganize their professional, social, and family lives.